(untitled) (Research, Society and Development, 2022)
This article aims to present Innovative Practices in Biology Teaching at a Federal Network Application School and its contributions to the development of an innovative education. For the development of the methodological process that guides this investigation, we listed the qualitative approach of the data, as a type of research the case study, as a data collection technique, an analysis of the institution’s Political Pedagogical Project (PPP) was initially carried out, seeking to investigate whether the innovation was included in their identity document and later semi-structured interviews were carried out with five biology educators from the federal education network institution and the data were analyzed using the Bardin content analysis technique (1977). As a result of this investigation, we obtained that the investigated school has innovation as an institutional educational principle, established in its PPP, we also realize that the educators’ conception of innovation converges between them and also with the literature and, finally, many innovative practices developed at school, whether individually or institutionally, and which confirm both the innovative character of the school’s formative processes and that educators develop innovative practices in their educational practice.